Variation among Populations and Correlation among Seedling Characters of White Jabon (Neolamarckia cadamba (Roxb.) Bosser) under Drought and Water Logging Stress - Dede J. Sudrajat; Iskandar Z. Siregar; Nurul Khumaida; Ulfah J. Siregar; Irdika Mansur (Foresty Faculty of Hasanuddin University, 2016)
Drought and water logging stress are the most critical environmental factors that affect tree seedling survival and growth in the field. In this study, 12 populations of white jabon (Neolamarckia cadamba (Roxb.) Bosser) were evaluated to determine the genetic variability among populations and correlation among morphophysiological seedling characters under drought and water logging stresses. Two research units were carried out by the randomized complete design with 2 x 12 factorial arrangements, i.e. (1) drought stress (2 treatments) and population (12 populations), and (2) water logging stress (2 treatments) and population (12 populations). Results showed that the responses of seedling traits were varied among populations under drought and waterlogging stresses. White Jabon seedling has higher adaptation to water logging stress than to drought stress. Kampar and Gowa populations have better adaptation to water logging stress. In drought stress, Gowa population had better adaptation followed by Nusa Kambangan population. Seedling height, total biomass and proline content characters based on value of broad sense heritability and correlation among characters, could be considered as important indicators for improvement programs for drought tolerance, while in the water logging stress, height, total biomass, root length and leaf area could be considered as important indicators for improvement program of white Jabon for tolerance on waterlogged sites.